2013
DOI: 10.3390/su5041356
|View full text |Cite
|
Sign up to set email alerts
|

From Talloires to Turin: A Critical Discourse Analysis of Declarations for Sustainability in Higher Education

Abstract: Declarations for sustainability in higher education are often seen as a set of guiding principles that aid institutions of higher learning to incorporate the concept of sustainability into their various institutional dimensions. As the Decade of Education for Sustainable Development draws to a close and in the shadow of the 20th anniversary of the Earth Summit in Rio de Janeiro, it seems appropriate to re-evaluate how these declarations have changed over the past two decades. In this study, we apply critical d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
31
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 37 publications
(49 reference statements)
0
31
1
Order By: Relevance
“…In higher education specifically, results indicate mixed outcomes in terms of the depth of engagement of universities, students, and faculty (Wals 2012, p. 86). Ashford (2004) has suggested that important concepts and values of Education for Sustainable Development (ESD), including ideological challenges to mainstream approaches, can be swallowed up by the restrictions of institutional curriculum constraints, which are "arguably undergoing a process of neo-liberalisation" (Sylvestre et al 2013(Sylvestre et al , p. 1358.…”
Section: Introductionmentioning
confidence: 99%
“…In higher education specifically, results indicate mixed outcomes in terms of the depth of engagement of universities, students, and faculty (Wals 2012, p. 86). Ashford (2004) has suggested that important concepts and values of Education for Sustainable Development (ESD), including ideological challenges to mainstream approaches, can be swallowed up by the restrictions of institutional curriculum constraints, which are "arguably undergoing a process of neo-liberalisation" (Sylvestre et al 2013(Sylvestre et al , p. 1358.…”
Section: Introductionmentioning
confidence: 99%
“…To some degree, HEIs have responded to this call to action, as evidenced by the signing of international sustainability in higher education declarations [6][7][8], the proliferation of sustainability in higher education publications [9], and the creation of organizations like the Association for the Advancement of Sustainability in Higher Education (AASHE). Further, many universities have begun developing sustainability policies and plans for their individual institutions [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Some HEIs have developed and signed declarations, initiatives, and charters to help them demonstrate their SD engagement to their students and other stakeholders, and integrate SD holistically into their system, including education, research, community outreach, operations, assessment and reporting, university collaboration, the institutional framework, educate-the-educator programs, and campus experiences [9][10][11]. The integration of SD in HEIs requires a focus on the elements of the HEI system, on making SD part of the higher education culture, and on ensuring the institutionalization of SD in HEIs [5,8,12].…”
Section: Introductionmentioning
confidence: 99%